Construction and evaluation of a carbon paste electrode modified with polyaniline-co-poly(dithiodianiline) for enhanced stripping voltammetric determination of metal ions - Somerset, Vernon; Silwana, Bongiwe; Horst, Charlton van der; Iwuoha, Emmanuel (Univerzita Pardubice, 2014)
A modified carbon paste electrodes (MCPE) have been prepared in this study as an alternative “mercury-free” electrochemical sensor for the determination of Pb2+ and Cd2+ metal ions in aqueous solutions. CPE containing a conducting copolymer of polyaniline-co-poly(2,2'- dithiodianiline) (PANI-co-PDTDA) was used as a modified substrate transducer to achieve enhanced selectivity in stripping voltammetric analysis. The experimental conditions optimised included the supporting electrolyte pH, deposition potential (Ed) and time (td), set at −0.6 V vs. ref. for Pb2+ and −0.8 V for Cd2+; both kept for td = 120 s. The results with the CPE/PANI-co- PDTDA sensor have revealed the linear range within the range of 0.15 – 0.5 μg/L for Pb2+ and the same interval for Cd2+. Finally, the electrode of interest, CPE/PANI-co-PDTDA, can be characterised by the LODs of 0.03 and 0.09 μg/L for Pb2+ and Cd2+ respectively.
Keywords: carbon paste electrode; PANI-co-PDTDA; differential pulse anodic stripping voltammetry; lead and cadmium; determination